Effect of Glycosaminoglycan Replacement on Markers of Interstitial Cystitis In Vitro - Rooney, Peadar; Ryan, Christina; McDermott, Barry J.; Dev, Kapil; Pandit, Abhay; Quinlan, Leo R. (Frontiers in Pharmacology, 2020)
Aims: To examine the effect of three commercial intravesical formulations of glycosaminoglycan on in vitro inflammatory models of IC/BPS to better understand there effect on specific markers of disease. Methods: Human urothelial cells (HTB-4) were cultured under four conditions in the presence or absence of commercial GAG formulations. Cells were cultured under a basal condition or pre-treated with protamine sulphate (100 ng/ml) (damages the endogenous glycosaminoglycan layer), hydrogen peroxide (1%) (a metabolic stressor) or TNFα (10 ng/ml) (creating an inflammatory environment). Each of these four culture conditions was then treated with one of three GAG formulations, CystistatⓇ, iAluRilⓇ and HyacystⓇ. Assays were then performed to examine the effect of the exogenous GAGs on cell viability, cell migration, sGAG production, cytokine and gene expression. Results: All GAG formulations were well tolerated by the HTB-4 cells and supported cell growth and migration. iAluRilⓇ was most effective at stimulating endogenous sGAG production under all conditions, increasing sGAGs by up to 15-fold. All GAG formulations significantly reduced the production of the pro-inflammatory cytokine IL-8 under basal conditions, while no GAG treatment suppressed cytokine production under any other condition. Only CystistatⓇ had a significant effect on HA receptor expression, significantly increasing ICAM-1 expression at 3 hours that returned to basal levels at 24 hours. No GAG treatment significantly changed the expression of GAG synthesis enzymes (CSGALNACT1, CSGALNACT2) or markers of tissue remodeling (MMP2, TIMP1) and pain (COX-1/PTGS-1, NGF). Conclusions: The data presented in this study reveal that commercial intravesical formulation support cell viability and migration. In addition, the commercial GAG formulations have a mild anti-inflammatory effect in the in vitro model of interstitial cystitis/bladder pain syndrome.